Penerapan Teknologi Revolusi Industri 4.0 Pada Lahan Pertanian Untuk Menunjang Produktifitas Pertanian Masyarakat Di Desa Tolnaku Kecamatan Fatuleu Kabupaten Kupang Nusa Tenggara Timur - Chr. Mauko, Imanuel; A. Wadu, Robinson; Nicodemus, Nicodemus; Abdullah, Yulian (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The Tamnau Tetus Farmers Group and the Hidup Baru Farmers Group are partners in the implementation of the Technology Application Grant Program Disseminated to the Community in Tolnaku Village, Fatuleu District, Kupang Regency, NTT. The partner problem is the issue of land irrigation, in which both groups of partners, difficult to irrigate agricultural land because the springs are at a lower altitude than agricultural land. In addition, during the dry season, many springs become dry, so that gardening activities are carried out more during the rainy season.Through this community service program, a technology based on the industrial revolution 4.0 will be applied, namely an automatic plant watering control system that distributes water to partner farms through a piping system using an energy-efficient Solar Power Plant (PLTS).As a result, it can be seen that the application of PLTS-based Automatic Plant Watering System technology can provide benefits including, the availability of a good clean water distribution system equipped with a piping system, water use is more efficient because it uses an automatic garden watering control system based on soil dryness and uses a water-saving sprinkler system and faster land watering time. There is also the availability of land that will be managed to become an agro-tourism location on the plantation land of the two partner groups